An Investigation of the Role of Advertising on Consumers’ Purchase Behavior – A Conceptual Analysis: Examining the Impact of Advertising on Consumer Purchase Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This paper centers on the influential role of advertising on consumer’s purchasing behavior. Brand impression, persuasion, and personality commendation as attributes that advance intent of the purchasers to the product and also influence the purchasing behavior. The study reconnoiters that imaginative and intensive drafting of advertisements has continuously a notable influence on the purchasing propensities of the consumers. The superiority of the artifact and value is also encompassed with their intense influence on the buying behavior of consumers.